Adaptive system for blood flow estimation - da Cruz Silva Andrade Madeira e Carvalho de Moura, Maria Margarida (2015)
Adaptive estimation of blood flow signals is performed resorting to a framework developed to support research on Doppler blood flow signals' analysis. Real time spectral estimation methods, real time performance evaluation and run-time adjustment of the estimation methods parameters are bound together allowing the system to adapt itself to varying signal characteristic that are caused by physiological reasons.